Expert Consensus to Examine the Cross-Cultural Utility of Substance Use and Mental Health Assessment Instruments for Use with Indigenous Clients. (September 2017) - Stephens, Anne; Bohanna, India; Graham, Deborah
Evaluation of minority-culture specific treatment centres for substance use and mental health is challenging. The challenge is compounded by a paucity of validated instruments for assessing substance use and mental ill health. In the field of Australian Indigenous alcohol and other drug service provision there are few guidelines to determine which instruments should be targets for validation for use with Indigenous clients. As such, reliable, validated, evaluable data on the client population is limited, posing multifaceted concerns for clinicians and service providers as well as evaluators. The aim of this study was to pilot the use of a participatory expert consensus approach to evaluate, rate and select suitable majority-culture substance use and mental health assessment instruments for use with their clients. Eight practitioners of an Indigenous-specific substance misuse residential treatment centre participated. The findings reinforce the value of consensus approaches for stakeholder engagement and to provide a sense of ownership of the results. In this setting, consensus on the implementation of an agreed set of Indigenous-specific and non-Indigenous specific instruments improved the ownership of the instruments by clinicians allowing for the use of valid and/or reliable instruments that also had good face validity. This makes it more probable that reliable client wellbeing data will be collected. This is crucial to program evaluation at a later point in time. This study was a novel approach to generating evidence to inform practice in the absence of normative practice guidelines.